Singlet–triplet separation induced by the Pseudo Jahn–Teller effect examples: The CX2 and NX2+ (X=H, Cl) molecules - Liu, Yang (Computational and theoretical chemistry, 2014)
[Display omitted] •The 3B1 states of CH2, CCl2, NH2+, NCl2+ are formed because of PJTE (3Σg-+3Πu)⊗πu.•The 1A1 and 1B1 bent structures result from combined PJTE (1Δg+1Πu)⊗πu and RTE of 1Δg state.•Spin-crossover induced by PJTE explains reversed-order of singlet/triplet ground state in CH2(NH2+) and CCl2(NCl2+).•Different singlet–triplet separation is rationalized by different Jahn–Teller vibronic coupling intensity. A theoretical investigation with high-level multireference methods is performed to reveal the Jahn–Teller origin of the triplet and singlet bent structures for CH2, CCl2, NH2+, and NCl2+ molecules and rationalize the relative energy ordering of the lowest singlet and triplet states. At the highest-symmetry linear configurations of these triatomic systems, the Pseudo Jahn–Teller effect (PJTE) between the ground state 3Σg- and excited state 3Πu upon the bending mode, denoted as (3Σg-+3Πu)⊗πu, is the reason of producing triplet 3B1 bent structures, and the combined PJTE of (1Δg+1Πu)⊗πu and Renner–Teller effect (RTE) of 1Δg state result in the formations of singlet 1A1 and 1B1 minima. The PJTE of “Δ–Π” plays a dominant role for the instability of degenerate Delta state which is subject to RTE. The spin-crossover induced by PJTE is responsible for the reversed order of singlet and triplet ground states in CH2/NH2+ and CCl2/NCl2+. The different singlet–triplet energy separations of those molecules can be rationalized from different Jahn–Teller vibronic coupling intensity at linear configurations.